P563 Association between smoking status and the efficacy and safety of tofacitinib in patients with Ulcerative Colitis: Data from the tofacitinib clinical programme. (21st January 2022) - Rubin, D T; Torres, J; Regueiro, M; Reinisch, W; Prideaux, L; Kotze, P G; Tan, F H; Gardiner, S; Mundayat, R; Cadatal, M J; Ng, S C
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis (UC). Efficacy and safety of tofacitinib were evaluated in randomised, placebo-controlled Phase (P)2 (NCT00787202) and P3 (NCT01465763; NCT01458951; NCT01458574) studies, an open-label, long-term extension (OLE) study (NCT01470612) and an ongoing P3b/4 study (NCT03281304). Ex-smokers have an increased risk of UC, but the response to therapy in these patients (pts) has not been previously evaluated. We assessed the impact of smoking status on the efficacy and safety of tofacitinib in the UC clinical programme. Methods: Efficacy endpoints and adverse events (AEs) were evaluated by smoking status (ever smokers [current and ex-smokers] and never smokers) in P2 (safety only)/P3/OLE/P3b/4 studies. Efficacy endpoints were summarised by treatment allocation; pt characteristics and AEs were summarised by tofacitinib predominant dose. Results: This analysis included 1156 pts (ever smokers, n=416 [36.0%; current smokers, n=59 (5.1%); ex-smokers, n=357 (30.9%)]; never smokers, n=740 [64.0%]; Table 1). Compared with never smokers, ever smokers were older and more likely to have a prior history of myocardial infarction, diabetes mellitus, or ischaemic or coronary heart disease. The proportion of pts achieving efficacy endpoints was generally similar across tofacitinib treatment groups regardless of smoking status (Table 2). AEs were reported in 88.7% of ever smokers and 83.8% of never smokers. Overall, 60.6% of ever smokers had an infection, specifically 10.8% had herpes zoster (non-serious and serious), 12.0% had a Clostridioides difficile infection and 19.5% had a lower respiratory tract infection; corresponding values for each AE among never smokers were 53.1%, 6.8%, 8.5% and 11.4% (Table 1). Major adverse cardiovascular events were reported in 1.0% of ever smokers and 0.7% of never smokers; thromboembolic events were reported in 1.0% of ever smokers and 0.9% of never smokers. Malignancies (excl. non-melanoma skin cancer [NMSC]) occurred in 2.5% of ever smokers and 1.5% of never smokers; NMSC occurred in 3.7% and 1.0%, respectively. In total, 0.6% of never smokers had colorectal cancer and there were no cases in ever smokers. Conclusion: The efficacy and safety of tofacitinib were generally similar in ever smokers and never smokers. This study is limited by the combined analysis of current and ex-smokers and unknown factors such as the degree of smoking and the time between smoking cessation and UC diagnosis. These data are consistent with previous reports in the general population and pts with UC. 1, 2 References: 1. Meserve J et al. Clin Gastroenterol Hepatol 2019; 7: 1533–1540. 2. Rogers MA et al. PLoS One 2012; 7: e42091.